1997
DOI: 10.1021/jp9702558
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Base Sites on Calcined Mg−Ga Hydrotalcite-like [Mg1-xGax(OH)2](CO3)x/2·mH2O

Abstract: A series of Ga-substituted hydrotalcite-like materials (GaHTs), [Mg 1-x Ga x (OH) 2 ](CO 3 ) x/2 ‚mH 2 O where x ) 0.12-0.36, were prepared in order to examine their textural and basic properties upon different Mg/Ga contents and calcination temperature. Specific surface area increases from 46 to 156 m 2 g -1 (Mg/Ga ) 7.7) when calcining from 523 to 673 K as a consequence of dehydroxylation and decarbonation of the material. The total number of base sites increases upon higher calcination temperatures until re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…The results for the mixed oxides containing Mg (Figs. 2a and 2b) were similar to those reported by López-Salinas et al (14); the strongest peak was also that observed at the highest temperature, so, as in MgO-600, the strongest basic sites predominate over those of medium and low strength. The two calcium-containing solids (HT-Ca/Al-500 and CaO-900) possess much smaller numbers of basic sites than the other catalysts; CaO-900 is similar to Mg-600 in that it abounds with strong basic sites, whereas CaO/Al 2 O 3 contains weak sites predominantly.…”
Section: and 264supporting
confidence: 88%
“…The results for the mixed oxides containing Mg (Figs. 2a and 2b) were similar to those reported by López-Salinas et al (14); the strongest peak was also that observed at the highest temperature, so, as in MgO-600, the strongest basic sites predominate over those of medium and low strength. The two calcium-containing solids (HT-Ca/Al-500 and CaO-900) possess much smaller numbers of basic sites than the other catalysts; CaO-900 is similar to Mg-600 in that it abounds with strong basic sites, whereas CaO/Al 2 O 3 contains weak sites predominantly.…”
Section: and 264supporting
confidence: 88%
“…Hydrotalcites-like compounds (HT) were synthesized considering the techniques reported by López-Salinas et al (24) and Hesiquio-Garduño et al (25) as follows: two mixed aqueous solutions, the first one composed of M(NO 3 ) 2 and Al(NO 3 ) 3 , and the second of KOH and K 2 CO 3 were added to hot deionized water (333 K) maintaining a M 2þ :Al 3þ ratio of 2:1. The pH during reaction was around 10 and it was controlled using KOH and K 2 CO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Here we report the results of a combined 1 H and 71 Ga SSNMR study of magnesium gallium (MgGa) LDH's with nitrate intercalated prepared using co-precipitation [Mg1-xGax(NO3)x yH2O] [19,20]. Gallium has two NMR active isotopes, 69 Ga and 71 Ga, which are both quadrupolar nuclei (I = 3/2) with high Larmor frequencies of which the latter is generally preferred due to a smaller quadrupole moment.…”
Section: Introductionmentioning
confidence: 99%